2009
DOI: 10.3341/jkos.2009.50.11.1624
|View full text |Cite
|
Sign up to set email alerts
|

2007 Survey for KSCRS Members - Current Trends in Cataract Surgery in Korea -

Abstract: Purpose: This study investigated the current situation and future trends in the field of cataract surgery in Korea. Methods: Since 1995, the members of the Korean Society of Cataract and Refractive Surgery (KSCRS) have conducted annual surveys regarding cataract and refractive surgery. The 2007 annual survey, consisting of 85 multiple-choice questions, was mailed in February 2008 to 301 KSCRS members. Sixty-two (20.6%) members answered the questions. Current data were compared with data from previous annual su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…The most commonly prescribed topical antibiotic after cataract surgery reported by the Survey of Korean Society of Cataract and Refractive Surgery was fluoroquinolone, which increased from 78% in 2007 to 85% in 2012. Among them, the frequency of prescriptions for moxifloxacin, a third-generation fluoroquinolone, rose sharply from 11% in 2007 to 44% in 2012 [ 21 , 22 ]. The second difference was that the culture rate of Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly prescribed topical antibiotic after cataract surgery reported by the Survey of Korean Society of Cataract and Refractive Surgery was fluoroquinolone, which increased from 78% in 2007 to 85% in 2012. Among them, the frequency of prescriptions for moxifloxacin, a third-generation fluoroquinolone, rose sharply from 11% in 2007 to 44% in 2012 [ 21 , 22 ]. The second difference was that the culture rate of Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly prescribed topical antibiotic after cataract surgery reported by the Survey of Korean Society of Cataract and Refractive Surgery was uoroquinolone, which increased from 78% in 2007 to 85% in 2012. Among them, the frequency of prescriptions for moxi oxacin, a third-generation uoroquinolone, rose sharply from 11% in 2007 to 44% in 2012 [21,22]. The second difference was that the culture rate of Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In both the 2005 and 2007 surveys, LASIK was the most commonly performed refractive surgery and was preferred in cases with myopia of less than -8 D as well as measurements from -8 to -12 D [ 4 5 6 ]. However, surface ablation was preferred in cases with myopia of less than -8 D, and phakic IOL implantation was preferred in cases with myopia greater than -8 D. This study revealed a decreased incidence of postoperative pain and corneal haze following surface ablation over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%